The underpinning factors of NBA game-play performance: a systematic review (2001-2020) - Huyghe, T.; Alcaraz, P. E.; Calleja-González, J.; Bird, S. P. (The Physician and Sportsmedicine, 2022)
Objective Recognizing the high stakes associated with winning and losing in the National Basketball Association (NBA), a deep understanding of the underlying mechanisms of NBA game-play performance would provide substantial benefit to all stakeholders involved with preparing NBA players and teams for competitive success. To the best of the authors` knowledge, this systematic review presents the first attempt to systematically amalgamate and appraise the scientific literature published in the XXI Century, following a constraints-led approach (CLA). In particular, two underpinning factors of NBA game-play performance were investigated: (1) NBA player constraints (internal variables) and (2) NBA contextual constraints (external variables).